Significance of Candida species in patients with coronavirus disease - Gurung, Kishor; Pokhrel, Sandeep; Neupane, Dhan Raj; Pant, Prabesh; Gurung, Samjhana (Journal of Kathmandu Medical College, 2021)
Background: Respiratory fungal infection is a severe clinical condition especially in immune-compromised individuals. Secondary fungal infections as complications of severe coronavirus disease 2019 are on the rise. Objectives: This study was carried out to isolate the Candida species from coronavirus disease 2019 patients, identify different species of Candida and to show the significance of Candida species in coronavirus disease 2019 patients attending a dedicated hospital for coronavirus disease management. Methods: A hospital-based descriptive cross-sectional study was done in a period between 2nd Jestha to 23rd Ashad 2077 (16th May to 7th July 2021) in Nepalgunj Medical College, Kohalpur, Banke. The study included 100 Coronavirus disease 2019 patients. Sputum samples were taken and subjected to direct microscopy, cultured onto Sabouraud Dextrose Agar. Candida species were determined by standard microbiological methods. Informed consent was taken prior to participation in study. Data were analysed for simple descriptive analysis using Microsoft Office Excel. Results: Out of 100 sputum samples, 78 (78%) men and 22 (22%) women were included; Candida species were isolated from 36 (36%) patients. This study shows Candida species isolated higher in male and from 31-60 years of age group. Conclusion: We recommend that the investigation and identification of Candida may be routinely followed in the microbiology laboratories.